Effect of Solvency, Sales Growth, and Institutional Ownership on Tax Avoidance with Profitability as Moderating Variables in Indonesian Property and Real Estate Companies - Rusna Oktaviyani; Agus Munandar (Binus Business Review, 2017)
This research aimed to examine the effect of solvency, sales growth, and institutional ownership towards tax avoidance with profitability as a moderating variable. The sample was real estate and property companies listed on the Indonesia Stock Exchange in 2011-2015. The sample was selected using purposive sampling method to get sample about 31 companies. The data used moderated regression analysis. The results indicate that the solvency has significant and positive effect on tax avoidance. Meanwhile, sales growth and institutional ownership do not affect tax avoidance. Then, profitability can moderate the relationship between institutional ownership and tax avoidance.